Productive performance of hair lambs fed fresh orange (Citrus sinensis) residues substituting sorghum (Sorghum vulgare) grains - Villanueva, Zamira; Ibarra, M. A.; Z?rate, P.; Briones, F.; Escamilla, O. S.; Gonz?lez, A.; Guti?rrez, E. (Cuban Journal of Agricultural Science, 2013)
The effect of substituting in the diet sorghum grain for fresh orange residue was assessed in Dorper lambs, crossbred and confined. Its repercussion on weight gain, feed intake and feeding conversion was appraised. Twenty lambs with 15.75 + 4.3 kg of initial weight were used, assigned to a completely randomized design with four treatments (T1: 15 % fresh orange residue + 85 % concentrated feed; T2: 20 % fresh orange residue + 80 % of concentrated feed; T3: 25 % fresh orange residue + 75 % concentrated feed and T4: 30 % fresh orange residue + 70 % concentrated feed). Five repetitions per treatment were conducted. Besides, analysis of covariance for initial weight was also conducted. Significant differences (P < 0.05) between treatments were observed for daily weight gain (238.4, 220.4, 210.2 and 209.2 g), daily feed intake (1.35, 1.22, 1.07, 0.970 kg) and feeding conversion (5.2, 4.8, 4.3 and 3.8 kg/kg of increase) for the lambs consuming rations of 15, 20, 25 and 30 % of fresh orange residue, respectively. The fresh orange residue had CP content of 6.0 % and in vitro DM digestibility of 72.3 %. The results indicate that its inclusion in lambs? rations can be of up to 30 %, without diminishing the animals? productivity, reducing the ration costs translated into higher benefit. Key words: weight gain, feed intake, feeding conversion.